Empowerment of female farmers through catfish culinary in industrial areas - Yoyoh Jubaedah; Asep Maosul; Nenden Rani Rinekasari; Rakhmat Yusuf; Neni Rohaeni; Heni Hernawati (Jurnal Abmas, 2026)
Catfish farmers face marketing challenges, resulting in delayed harvests and significant price declines. This program aims to improve the economic capacity of women's farmer groups through catfish-based culinary training in Sukamanah Village, Rancaekek District, an area impacted by industrial waste. The method used was a participatory, learning-by-doing model and a Training-of-Trainers (ToT) approach. The program was implemented over six months, encompassing needs analysis, training, mentoring, and evaluation. Results showed significant improvements in participants' knowledge, food processing skills, and product innovation capabilities. The resulting products, such as siomay (siomay), tofu meatballs, and fried catfish dumplings, have a high level of acceptance and have the potential to become household-based micro-enterprises. This program also contributes to women's empowerment by increasing productivity and family income. Furthermore, the digital-based mentoring approach and the role of PKK (Family Welfare Movement) cadres as local agents have proven to support the program's sustainability. Thus, culinary training based on local potential can be an effective strategy for improving family welfare in areas affected by industrial pollution.   Abstrak Para peternak ikan lele mengalami kesulitan dalam pemasaran, sehingga ikan terlambat dipanen dan harga jual menurun secara signifikan. Kegiatan ini bertujuan untuk meningkatkan kapasitas ekonomi wanita kelompok tani melalui pelatihan kuliner berbasis ikan lele di Desa Sukamanah, Kecamatan Rancaekek, yang merupakan wilayah terdampak limbah industri. Metode yang digunakan adalah pendekatan partisipatif berbasis model learning by doing dan pendekatan Training-of-Trainers (ToT). Kegiatan dilaksanakan selama enam bulan melalui tahapan analisis kebutuhan, pelatihan, pendampingan, dan evaluasi. Hasil menunjukkan adanya peningkatan signifikan dalam pengetahuan, keterampilan pengolahan pangan, serta kemampuan inovasi produk peserta. Produk yang dihasilkan berupa siomay, baso tahu, dan pangsit goreng ikan lele memiliki tingkat penerimaan yang tinggi dan berpotensi menjadi usaha mikro berbasis rumah tangga. Program ini juga berkontribusi terhadap pemberdayaan perempuan melalui peningkatan produktivitas dan pendapatan keluarga. Selain itu, pendekatan pendampingan berbasis digital dan peran kader PKK sebagai agen lokal terbukti mendukung keberlanjutan program. Demikian, pelatihan kuliner berbasis potensi lokal dapat menjadi strategi yang efektif untuk meningkatkan kesejahteraan keluarga di wilayah yang terdampak oleh pencemaran industri. Kata Kunci: diversifikasi produk pangan; ikan lele; kesejahteraan keluarga; pemberdayaan wanita tani